Sosialisasi Pemanfaatan Pewarna Alami Pada Sel Surya di MAS Darrul Mukarram Barito Kuala - Trianiza, Ice; Sidiq, Abdurahim; Muttaqin, Idzani; Muammar, Rais; Hidayati, Tazkia; Ahmad, Rizky Yanuar (Yayasan Sagita Akademia Maju, 2024)
As many as 44 students have carried out community service at MAS DaruL Mukarram with the title socialization on the use of natural dyes in solar cells. The aim of this service is to educate students to have knowledge, be creative, apply and teach in society about one of the alternative energies in the form of solar cells based on natural raw materials. As for the results of knowledge regarding this socialization, there was an increase in students' understanding, as seen by the students' average score of 92.5 during the post test